Recovery of early postoperative muscle strength after deep neuromuscular block by means of ultrasonography with comparison of neostigmine versus sugammadex as reversal drugs: study protocol for a randomised controlled trial. Issue 2 (26th February 2021) - Wang, Xuan; Li, Yingyuan; Huang, Chanyan; Xiong, Wei; Zhou, Qin; Niu, Lijun; Xiao, Ying
Abstract : Introduction: Despite the use of quantitative neuromuscular monitoring together with the administration of reversal drugs (neostigmine or sugammadex), the incidence of residual neuromuscular blockade defined as a train-of-four ratio (TOFr) <0.9 remains high. Even TOFr >0.9 cannot ensure adequate recovery of neuromuscular function when T1 height is not recovered completely. Thus, a mathematical correction of TOFr needs to be applied because the return of a normal TOFr can precede the return of a normal T1 twitch height. On the other hand, different muscles have different sensitivities to neuromuscular blockade agents; thus, complete recovery of one specific muscle group does not represent complete recovery of all other muscles. Therefore, our study aims to assess the muscle strength recovery of respiratory-related muscle groups by ultrasound and evaluate global strength using handgrip dynamometry in the early postoperative period when TOFr=0.9 and corrected TOFr (cTOFr)=0.9 with comparison of neostigmine versus sugammadex as reversal drugs. Methods and analysis: This study will be a prospective, single-blinded, randomised controlled trial involving 60 patients with American Society of Anesthesiologists physical status I–II and aged between 18 and 65 years, who will undergo microlaryngeal surgery. We will assess geniohyoid muscle, parasternal intercostal muscle, diaphragm, abdominal wall muscle and handgrip strength at four time points: before anaesthesia, TOFr=0.9, cTOFr=0.9 and 30 min after admission to the post anaesthesia care unit. Our primary objective will be to compare the effects of neostigmine and sugammadex on the recovery of muscle strength of different muscle groups in the early postoperative period when TOFr=0.9 and cTOFr=0.9. The secondary objective will be to observe the difference of muscle strength between the time points of TOFr=0.9 and cTOFr=0.9 to find out the clinical significance of cTOFr >0.9. Ethics and dissemination: The protocol was reviewed and approved by the Ethics Committee of The First Affiliated Hospital, Sun Yat-sen University. The findings will be disseminated to the public through peer-reviewed scientific journals. Trial registration number: ChiCTR2000033832.